Upgrading Skill Kewirausahaan Siswa SMK Melalui Pelatihan Penyusunan Business Model Canvass Berbasis Digital - Elvi Rahmi; Efni Cerya; Friyatmi Friyatmi (Universitas Negeri Padang, 2022)
One of the formal educational institutions, namely the Vocational High School (SMK), organizes vocational education at the secondary education level and trains students to work in certain professions. The current digital era opens wide opportunities for anyone to progress and develop, opportunities to start a business and do entrepreneurial activities are relatively easy to do. Improving the competence of students and teachers is the only way to overcome the dilemma regarding digital skills so that students are able to capture the digital business opportunities that surround them into productive business opportunities. This community partnership program is carried out at SMKN 1 Baso by providing training through ongoing guidance to students on making practical business plans using the Business Model Canvas (BMC). The results of activities at Baso 1 Vocational High School with training related to the preparation of the digital-based CANVAS business model were very useful where positive feedback from participants stated that the material presented was interesting, useful and motivated students to become young entrepreneurs.